International university rankings: application of indicators to institutional scientific production of the Universidad Central “Marta Abreu” of Las Villas in Scopus, 2015-2019 - Ramos Hernández, Cynthia (2021)
Aim: Indicators of international university rankings for institutional scientific production are described to help improve university positioning on an international scale. Methodology: The design is quantitative and bibliometric techniques were combined with documentary analysis. First, the Cuban positioning in the Scimago Institutions Ranking (SIR) is described at a global level and in the dimensions of indicators, then the scientific production of the Central University "Marta Abreu" of Las Villas (UCLV) is characterized, indexed in Scopus by some Scimago Institutions Ranking (SIR) indicators. Finally, the indicators of leadership, open access, number of citations and excellence between the UCLV and the University of Havana (UH) were compared in order to characterize the positions obtained in the SIR. Results: The positioning of the UCLV and the UH in the SIR is close, however the differences in the scientific production of the UH with respect to the UCLV are relevant. The UCLV has two faculties that provide the highest scientific production in Scopus (FMFC and FQF) and in total the institution obtained low results in the applied SIR indicators. At least 50% of the scientific production was carried out with leadership. Conclusions: The application of international university ranking indicators at the meso level enables a better understanding and approach to the positions obtained by the universities in the SIR. It offers information on what aspects to take into account to improve the positioning and therefore the international visibility of universities.The study is a pioneer in the application of ranking indicators in Cuban institutions to help improve their international positioning.